What women want (and need) from coaching relationships during business incubation. (3rd September 2022) - Maxheimer, Mariah M.; Nicholls-Nixon, Charlene L.
Abstract: This qualitative study explores what dimensions of entrepreneurial coaching matter to women during business incubation and why. This issue is important because Canada is a world leader in the rate of entrepreneurial activity and business incubation support, yet women are underrepresented and their coaching needs are not well understood. Purposive sampling was employed to recruit 15 participants (6 women, 5 men, 4 coaches) from four Canadian incubators. Data was collected using semi-structured interviews. NVivo software facilitated coding and gender comparisons. Analysis followed the Gioia methodology for grounded theorizing which revealed 52  second-order concepts that grouped into three primary coaching dimensions (venture support, emotional support, gender inclusivity). Men and women value these dimensions differently. The emergent theoretical model suggests that for women entrepreneurs, business expertise (a dimension of venture support), emotional support, and gender inclusivity influence the development of entrepreneurial self-efficacy (ESE), which, in turn, contributes to entrepreneurial outcomes (venture and personal development) during business incubation. The coach's personal investment and the entrepreneur's coachability influences these relationships. The findings have implications for future research exploring incubation as a gendered phenomenon, and for incubator managers and policy makers concerned with designing inclusive incubation programs and reducing the gender gap in Canadian entrepreneurship.